PELAKSANAAN TUGAS DAN WEWENANG HAKIM PENGAWAS DAN PENGAMAT PENGADILAN NEGERI DENPASAR DALAM PEMBINAAN NARAPIDANA - Suartha, I Dewa Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 2 (2014), 2014)
How is the implementation of duties and authorities of supervisors and observers judges of Denpasar District Court in founding the convict? What are obstacles that occur in implementation of duties and authorities of supervisors and observers judges of Denpasar District Court in founding the convict? The method used in this research was empirical legal research. Its characteristic is descriptive.  The data sources that used are primary data, secondary data and tertiary data. The primary data / field data were obtained by interviewing the relevant law enforcement officer that has been determined as a sample. The secondary data were obtained of literature studies. The data was analyzed by qualitative descriptive analysis to get the vivid conclusion and description in discussing the problems in this research. Conclusions derived from this study include: implementation of duties and authorities of supervisors and observers judges of Denpasar District Court in founding the convict are not running optimally in accordance with the legislation in force. The factor that obstruct are the numbers of supervisors and observers judges of Denpasar District Court were not adequate, that was one person, there was no special fund (Operational fund) and there were no strict sanctions for those when they could not do the duties according to the applicable law; they could only appeal to the law enforcement agencies / officers of Class IIA Denpasar Penitentiary founding the convict.
Keywords: founding the convict; supervisors; observers judges